Peran dan keterampilan pustakawan pada era digital di Perpustakaan UIN Imam Bonjol Padang - Delvalina, Delvalina; Ismail, Lusi; Makdis, Nasrul; Yuniati, Amelia; Farida, Mutia (Al-Kuttab : Jurnal Kajian Perpustakaan, Informasi dan Kearsipan, 2025)
The rapid development of information technology has brought significant changes to library services; however, not all librarians are adequately prepared to face this transformation. A lack of mastery in digital technologies and non-technical skills has become an obstacle to delivering effective services. This study discusses the essential skills that librarians need to possess in the digital era to address these challenges. The aim of this research is to describe the various competencies required for librarians to manage library services effectively and adaptively amid digital transformation. This research is a qualitative library study using a descriptive approach to analyze relevant primary and secondary data. The findings show that librarians are expected to master both technical skills related to information technology (IQ skills) and social-emotional skills (EQ skills), such as communication, adaptability, and quality service. These skills are crucial for enabling librarians to meet the demands of the digital age and to position libraries as relevant and appealing sources of information for the digital generation. Therefore, comprehensive competency development for librarians is a strategic step toward establishing a globally competitive digital library.